2021
DOI: 10.1002/path.5797
|View full text |Cite
|
Sign up to set email alerts
|

The utility of color normalization for AI‐based diagnosis of hematoxylin and eosin‐stained pathology images

Abstract: The color variation of hematoxylin and eosin (H&E)-stained tissues has presented a challenge for applications of artificial intelligence (AI) in digital pathology. Many color normalization algorithms have been developed in recent years in order to reduce the color variation between H&E images. However, previous efforts in benchmarking these algorithms have produced conflicting results and none have sufficiently assessed the efficacy of the various color normalization methods for improving diagnostic performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…Many previous studies introduced color normalization methods to minimize staining inconsistencies ( 29 , 37 ). Though it is hard to measure the preservation of diagnostic information after image transformation, many integrative studies investigating cancer subtype classification and prognosis association achieved optimistic performances by introducing image normalization ( 38 , 39 ). From this point of view, color normalization could be beneficial for assorted research cohort from miscellaneous data sources, especially from multiple institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies introduced color normalization methods to minimize staining inconsistencies ( 29 , 37 ). Though it is hard to measure the preservation of diagnostic information after image transformation, many integrative studies investigating cancer subtype classification and prognosis association achieved optimistic performances by introducing image normalization ( 38 , 39 ). From this point of view, color normalization could be beneficial for assorted research cohort from miscellaneous data sources, especially from multiple institutions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previously mentioned studies, they reported a significant gain in performance with the color normalization of [113]. Finally, in [141], the influence of several color normalization algorithms [100], [103], [106], [108], [111], [113] has been studied for the classification of three different histological cancer H&E WSIs (ovarian, breast, and pleural) using a ResNet18 network. Their finding is that color normalization does not improve performance when WSIs are from the same center.…”
Section: ) Influence Of Colormentioning
confidence: 90%
“…To enhance the generalization of the model, validation experiments on data from multiple sources are necessary. Meanwhile data batch effects [ 194 ] place high demands on data preprocessing [ 195 ]. For addressing the data noise problem, standardized data preprocessing systems [ 196 , 197 ] or uniform collection standards should be proposed accordingly.…”
Section: Opportunities and Challenges In Ai-based Pathologymentioning
confidence: 99%